Pengembangan Sistem Pendukung Keputusan Berbasis Web untuk Seleksi Penerima KIP-Kuliah dengan Metode Fuzzy Tsukamoto - Furqon, Muhamad (Ma'soem University, 2025)
Ma’soem University, as one of the private higher education institutions, provides scholarships for outstanding and underprivileged students. However, the selection process for the KIP-Kuliah scholarship faces challenges due to limited quotas and a high number of applicants. In developing this system, the author adopts a descriptive method to collect the necessary data and information. Meanwhile, for system design, the Waterfall method is utilized in a systematic and sequential manner, covering analysis, design, coding, and testing stages. The system design also incorporates the Unified Modeling Language (UML), including Use Case Diagrams and Class Diagrams. The Decision Support System application is implemented using the PHP (Hypertext Preprocessor) web programming language and a MySQL database. The results showed that development of this decision support system will assist the student affairs department in determining suitable scholarship recipients based on predefined criteria, thereby making the scholarship selection process more efficient and effective.